Awareness of occupational health hazards and occupational stress among dental care professionals: Evidence from the GCC region - AlDhaen, Esra (Frontiers in Public Health, 2022)
A hazardous work environment creates critical concerns, and resultantly, workers may suffer from job-related stress. So, this study aimed at identifying the nature of hazards prevailing in dental hospitals and their role in increasing job-related stress. The study also assumes that awareness of the existence of health hazards and their possible risk will originate the stress. To conduct the study, close-ended questionnaires were administered to 300 workers having more than 1 year of experience in Oral and Dental Health Services provided by the Kingdom of Bahrain. In total, 222 responses with an acceptable level of accuracy were included for statistical treatment. Results confirmed the prevalence of ergonomic, biological, physical, and, to some extent, chemical hazards in the workplace. Results revealed that stress befalls the employees as they know their exposure to these hazards. Ergonomic hazards have the highest prevalence, chemical hazards are the least prevalent, while biological and physical hazards fall in between. This study enriches the related bank of literature by tapping the hazards specifically in the dental hospitals' environment with the degree of intensity of their prevalence within the context at hand. The study of the impact of these workplace health hazards on occupational stress with mediating effect of awareness is also an addition to the existing literature. The findings may help hospital administrators to take correct measures to manage job-related stress that is counterproductive and take remedial steps to mitigate these hazards.